2015
DOI: 10.1007/978-3-319-25591-0_24
|View full text |Cite
|
Sign up to set email alerts
|

Interactively Illustrating the Context-Sensitivity of Aristotelian Diagrams

Abstract: Abstract. This paper studies the logical context-sensitivity of Aristotelian diagrams. I propose a new account of measuring this type of context-sensitivity, and illustrate it by means of a small-scale example. Next, I turn toward a more large-scale case study, based on Aristotelian diagrams for the categorical statements with subject negation. On the practical side, I describe an interactive application that can help to explain and illustrate the phenomenon of context-sensitivity in this particular case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…In the research program of logical geometry (see www.logicalgeometry.org), we study Aristotelian diagrams as objects of independent mathematical interest, i.e., regardless of any of their specific applications. We focus on logical issues such as informativity, Boolean complexity and logic-sensitivity [50][51][52], but also on more visual/diagrammatic aspects, such as informational vs. computational equivalence of Aristotelian diagrams [53][54][55]. One of the crucial insights in this area is that Aristotelian diagrams can also be fruitfully seen as truly geometrical entities and studied by means of tools and techniques such as projection matrices, Euclidean distance, symmetry groups, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the research program of logical geometry (see www.logicalgeometry.org), we study Aristotelian diagrams as objects of independent mathematical interest, i.e., regardless of any of their specific applications. We focus on logical issues such as informativity, Boolean complexity and logic-sensitivity [50][51][52], but also on more visual/diagrammatic aspects, such as informational vs. computational equivalence of Aristotelian diagrams [53][54][55]. One of the crucial insights in this area is that Aristotelian diagrams can also be fruitfully seen as truly geometrical entities and studied by means of tools and techniques such as projection matrices, Euclidean distance, symmetry groups, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In Subsection 6.1, however, we showed that these relations can also be used to define an Aristotelian square, but whether this square is classical or degenerated, depends on whether the relations' first argument is assumed to be satisfiable; compare Figure 24(a) and (b). Similarly, the six relations in the duality diagram shown in Figure 33(a) can also be used to define an Aristotelian hexagon, but whether this is a JSB or a U4 hexagon again depends on whether the relations' first argument is assumed to be satisfiable; compare Figure 25 This sharp contrast between Aristotelian and duality diagrams can be seen as the metalogical manifestation of a more general phenomenon that is well-understood at the object-logical level: the Aristotelian relations are sensitive to the deductive power of the underlying logical system, but the duality relations are entirely insensitive to this [23]. 51 Consider, for example, the formulas p and ¬p from modal logic.…”
Section: Resultsmentioning
confidence: 99%
“…the Aristotelian diagram that is obtained by adding the complements of all relations that occur in the original diagram. 23 The resulting diagram is a dodecagon, which is shown in Figure 18. 20 The systematic study of such non-standard Aristotelian diagrams is still in its infancy; some preliminary results can be found in [60,61].…”
mentioning
confidence: 99%
See 2 more Smart Citations